Chiral dynamics of baryons in a Lorentz covariant quark model; Physical Review D; Vol. 73, iss. 11 - Faessler A.; Gutsche Th.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Pumsa-ard K. (2006, 2006)
Title screen